What stands between self-disgust and borderline features? The need to cultivate self-compassion in adolescents from Portugal - Carreiras, Diogo (2021)
Borderline personality disorder (BPD) is characterized by emotional instability, unstable relationships, feelings of abandonment and emptiness, impulsivity, and self-harm. An unstable self-image is also a common borderline feature, often marked by self-criticism, self-hate and feeling of disgust towards aspects of the self. Considering the developmental path of BPD, it is essential to act at early ages with adolescents that show growing and persistent borderline features. The present study aimed to test the mediation role of self-compassion in the relationship between self-disgust and borderline features in Portuguese adolescents. Participants were 655 adolescents (381 girls and 274 boys) with an average of 15.58 years old (SD = 1.51), who completed self-report questionnaires at school. Data were analyzed through SPSS and PROCESS Macro to perform descriptive statistics, comparisons, correlations and regressions. Results showed that self-compassion mediated the relationship between self-disgust and borderline features. The mediation model explained 51% of borderline features and gender was used as a covariate, considering that girls exhibited higher self-disgust and borderline features, and lower self-compassion than boys. These findings indicate that cultivating self-compassion skills in adolescents could be a potential positive regulation mechanism for self-disgust's effect on borderline features.